A Critique and Evaluation of Methodology and Theory in Political Science - Elham Rasooli Saniabadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The main purpose of this study is to examine and evaluate the major strengths and weaknesses of David Marsh and Jerry Stoker's book entitled Methodology and Theory in Political Science. Since one of the most important areas of the philosophy of science is the field of transnational issues focusing on the issues of ontology, epistemology, and methodology, the main objective of this study is to bridge the gaps in two domains of epistemology and methodology. The book covers articles in three areas, including “ Political Science Approaches” , (Methodological Questions”, and “Theories about the Governments,” which were written by different authors from Britain universities, so these issues have been dealt with from a British approach. In this study, we first introduce the overall evaluation of the book, then we discuss the weaknesses and the disadvantages of the book. In the fifth section, the overall content evaluation of the book is presented, and in the final section, the most important strengths and disadvantages of the content of each chapter are enumerated. . This research is analytical with a critical approach through a case study.